Focal adhesion kinase as well as p130Cas and paxillin is crucially involved in the enhanced malignant properties under expression of ganglioside GD3 in melanoma cells - Hamamura, Kazunori; Tsuji, Momoko; Ohkawa, Yuki; Nakashima, Hideyuki; Miyazaki, Sayaka; Urano, Takeshi; Yamamoto, Noriyuki; Ueda, Minoru; Furukawa, Koichi; Furukawa, Keiko (Biochimica et biophysica acta, 2008)
Mass spectrometry analysis of immunoprecipitates from serum-treated GD3-expressing melanoma cells with PY20 (anti-phosphotyrosine antibody) revealed that focal adhesion kinase (FAK) is more strongly activated in GD3-expressing cells than in GD3-negative cells. Involvent of FAK in the increased proliferation and invasion in GD3-expressing melanomas was demonstrated by siRNA-mediated knockdown. Also, it was shown that FAK is located up-stream of p130Cas and paxillin in the enhanced signaling pathway. GD3 expression enhanced the association of FAK with p130Cas after treatment with fetal calf serum. Thus, focal adhesion kinase as well as p130Cas and paxillin should be a crucial molecule undergoing stronger tyrosine phosphorylation in GD3-expressing melanoma cells. Molecules linking GD3 and FAK such as integrins in the enhanced signaling pathway remain to be investigated.